Compostable polymer materials - Rudnik, Ewa (Elsevier, 2019)
An essential resource for graduate students and scientists working in chemistry, materials science, ecology, and environmental science, this book covers the entire spectrum of preparation, degradation, and environmental issues related to compostable polymers. -- Edited summary from book.
Keywords: Biodegradable plastics.; elektronické knihy; electronic books